Beyond the Visible???Imaging the Human Brain With Light - Obrig, Hellmuth; Villringer, Arno (Journal of cerebral blood flow and metabolism, 2003)
Optical approaches to investigate cerebral function and metabolism have long been applied in invasive studies. From the neuron cultured to the exposed cortex in the human during neurosurgical procedures, high spatial resolution can be reached and several processes such as membrane potential, cell swelling, metabolism of mitochondrial chromophores, and vascular response can be monitored, depending on the respective preparation. The authors focus on an extension of optical methods to the noninvasive application in the human. Starting with the pioneering work of Jöbsis 25 years ago, near-infrared spectroscopy (NIRS) has been used to investigate functional activation of the human cerebral cortex. Recently, several groups have started to use imaging systems that allow the generation of images of a larger area of the subject's head and, thereby, the production of maps of cortical oxygenation changes. Such images have a much lower spatial resolution compared with the invasively obtained optical images. The noninvasive NIRS images, however, can be obtained in undemanding set-ups that can be easily combined with other functional methods, in particular EEG. Moreover, NIRS is applicable to bedside use. The authors briefly review some of the abundant literature on intrinsic optical signals and the NIRS imaging studies of the past few years. The weaknesses and strengths of the approach are critically discussed. The authors conclude that NIRS imaging has two major advantages: it can address issues concerning neurovascular coupling in the human adult and can extend functional imaging approaches to the investigation of the diseased brain.